Laser Surface Structuring of Commercial Pure Titanium - Aseel Mohammed Al-Khafaji; Thekra Ismael. Hamad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim This Study existent laser surface structuring of commercial pure titanium (Ti) grade II dental implant,surface structuring of the titanium implant expected causing decrease the time of implant healing andaccelerated the periimplant bone formation. So the present study aimed was in vitro evaluation of commercialpure titanium when subjected to two laser surface structuring (dot and groove) in different laser scans andcomparing with titanium surface that not subjected to any surface structuring (control) by using opticalmicroscope, scanning electron microscope (SEM) and X-ray Diffraction analysis (XRD) test.Materials and Methods: CNC fiber laser machine laser was used for performing the structuring on thesurface of the commercial pure titanium (CP Ti) disks and then analyzed with the control group by opticalmicroscope, SEM and XRD test. The study groups are: polished CP Ti (control); (5, 15 and 25) CP Ti withdot design laser scans; (5, 15 and 25) CP Ti with groove design laser scans.Results the optical and SEM results showed a uniform homogenous structure on the surface of the CP Ti forthe two design of all tested laser scans (5, 15 and 25). The XRD results show an increasing in the titaniumoxide layer for the disks with laser structuring comparing to the control one which predicted to increasetitanium osseointegration while maintaining biocompatibility characteristics of the CP Ti.Conclusions: CNC fiber laser machine are successful method for CP Ti surface structuring. For both lasersurfaces structuring design, the 25 laser scan showed more promising results follow by 15 laser scan then 5laser scan and lastly the control group.